2006
DOI: 10.1084/jem.20061011
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes give rise to mucosal, but not splenic, conventional dendritic cells

Abstract: The mononuclear phagocyte (MP) system is a body-wide macrophage (MΦ) and dendritic cell (DC) network, which contributes to tissue homeostasis, inflammation, and immune defense. The in vivo origins of MPs remain poorly understood. Here, we use an adoptive precursor cell transfer strategy into MP-depleted mice to establish the in vivo differentiation sequence from a recently identified MΦ/DC-restricted bone marrow (BM) precursor (MDP) via BM and blood intermediates to peripheral MΦs and DCs. We show that MDPs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
529
6
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(585 citation statements)
references
References 57 publications
47
529
6
3
Order By: Relevance
“…The macrophage and DC precursor (MDP) for lymphoid tissue conventional DCs (cDCs), pDCs and monocytes is characterized as a cell expressing Lin À c-kit hi CD115 1 CX 3 CR1 1 Flt3 1 [8,26]. Another distinct progenitor is called the common DC precursor (CDP) (Lin À c-kit low CD115 1 Flt3 1 ) and is restricted to produce cDCs and pDCs, but not monocytes [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The macrophage and DC precursor (MDP) for lymphoid tissue conventional DCs (cDCs), pDCs and monocytes is characterized as a cell expressing Lin À c-kit hi CD115 1 CX 3 CR1 1 Flt3 1 [8,26]. Another distinct progenitor is called the common DC precursor (CDP) (Lin À c-kit low CD115 1 Flt3 1 ) and is restricted to produce cDCs and pDCs, but not monocytes [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Blood monocytes can be subdivided into at least two subsets based on their Ly6C expression: classical and The nonclassical monocytes, which are Ly6C low , patrol the endothelium of the blood vessels and are required for rapid tissue invasion at the site of an infection [7]. Ly6C low monocytes are considered CD11c À , but some studies have reported the expression of CD11c on these cells [6,8]. Both types of monocytes are F4/80 1 and CD86 À [6].…”
Section: Introductionmentioning
confidence: 99%
“…Is this parasite even able to act on cells in the bone marrow? Varol et al (2007) suggested that the old scheme of myeloid differentiation as a 'one way' intermediate from the bone marrow to the periphery has to be revised, as blood monocytes can efficiently home back to the bone marrow. Another group (Becker et al, 2005) found that CD8 þ memory T cells can also reside in the BM and thus can respond faster to antigens than cells residing in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments have elegantly shed light on how lung DC subsets develop. Using adoptive transfer studies of monocytes in mice depleted of cDC, as well as using a genetic lineage tracing system employing lysozyme (Lys)MCre  Stop/floxGFP as the reporter, it was shown that a large percentage of lung cDC do not derive from the Flt3 1 pre-cDC that seed the lymph nodes and spleen, but derive from circulating monocytes [12,19,20]. Contrasting these reports, two recent studies identified pre-cDC as the major contributing source for CD11b À CD103 1 lung cDC.…”
Section: Origin and Turnover Of Lung DC Subsetsmentioning
confidence: 99%